Searching for new predators of the invasive Halyomorpha halys: the role of the black garden ant Lasius niger. Issue 9 (3rd June 2021) - Bulgarini, Giacomo; Castracani, Cristina; Mori, Alessandra; Grasso, Donato A.; Maistrello, Lara
Abstract: In recent years, Halyomorpha halys (Stål) (Hemiptera: Pentatomidae, Cappaeini) has become an invasive pest in North America and Europe, where it caused extensive damage to agriculture, resulting in great economic losses. Evaluating the potential of native predators in the invaded areas, ants might represent good candidates thanks to their biology, ecology, and behavior. In Italy, H. halys proved to be the top key pest in pear orchards, where the black garden ant, Lasius niger (L.) (Hymenoptera: Formicidae, Lasiini), is the most abundant ant species. The aim of this study was to evaluate the predatory ability of L. niger on the eggs and on all the juvenile instars of H. halys under laboratory conditions. The results indicate that L. niger significantly reduces the survival of the second and third nymphal instars by 56 and 58%, respectively, but it is unable to reduce the egg hatching and the survival of the first, fourth, and fifth instars. Our preliminary results obtained in laboratory conditions suggest a possible role of the ant L. niger in controlling H. halys invasion mainly acting on the smaller and more mobile nymphal stages. The effective role of this species as potential biocontrol agents of H. halys in fruit orchards in association with other ant species as well as with other predatory insects is discussed. Abstract : The predatory potential of workers of the ant Lasius niger (Hymenoptera: Formicidae) was evaluated on eggs and nymphs of the agricultural pest Halyomorpha halys (Hemiptera: Pentatomidae). Egg hatching and survival of instars 1, 4, and 5 were not affected, but ants significantly reduced the survival of instars 2 and 3 by over 50%, attacking them especially on the ground. Therefore, a role for L. niger in conservation biological control of H. halys should be considered in association with other agents.